Wladimiro Acosta - Luis Müller (Docomomo Journal, 2022)
Wladimiro Acosta, a Russian-born architect, has been one of the key figures of twentieth-century architecture in Argentina. Together with his countryman and comrade Gregori Warchavchik, Acosta migrated to South America at the end of the 1920s: Warchavchik settled in Brazil, while Acosta came to Argentina.